Utilization of micro‒algal biomass residues (MABRS) for bio‒hythane production‒ a perspective - Krishnan, Santhana; Mohd Fadhil, Md Din; Shazwin, Mat Taib; Yong, Ee Ling; Eeyzah, Aminuddin; Chelliapan, Shreeshivasan; Mishra, Puranjan; Rana, Supriyanka; Mohd Nasrullah, Zulkifli; Mimi Sakinah, A. M.; Zularisam, A. W.; Singh, Lakhveer (MedCrave Group, 2018)
This contribution presents the technical possibilities for hydrogen and methane production from micro‒algal biomass residual wastes. Algal biomass is rich in carbohydrates which can be utilized as a promising source of substrate for dark fermentation. It becomes more significant when biomass is produced by capturing atmospheric greenhouse gas, CO2. In the present technical note, how clean energy can be generated in the form of bio‒hydrogen and methane utilizing algal biomass residues is discussed shortly. The scientific contribution of this two‒stage technology may play a significant role in degrading micro algal biomass in to zero waste and developing an energy‒efficient strategy for waste management.